Analysis Effect Blade Distance on the Performance of Microhydro Power Plants - Prihastuty, Endang; Yudisworo, Waluyo Djoko; Tohasan, Achmad; Maldiesa, Maldiesa; Subiyanta, Erfan (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2024)
Microhydro power plants are small-scale power plants that use hydropower as their driving force. The hydropower used can be in the form of water flows such as irrigation canals, rivers or natural waterfalls. Microhydro power plants principally utilize the height and amount of water flow discharge per second on the water flow of irrigation canals, rivers or waterfalls. This flow of water rotates the turbine shaft so as to produce mechanical energy. One of the components in microhydro power plants is a turbine. The type of turbine used in low-head water flow is a screw turbine. This study discusses the effect of blade distance on the performance of microhydro power plants. The change in blade spacing given is 15 cm, 20 cm and 22 cm spacing with a 40-degree blade slope. From changes in blade spacing greatly affect the power and efficiency of the turbine. The highest power is generated by the use of 15 cm blades of 1267 watts. The efficiency of the turbine is also affected by the power generated by the turbine itself. The highest turbine efficiency is produced by the use of a blade distance of 15 cm of 37.25%, the closer the distance between the blades the greater the power and efficiency generated in the turbine itself.